University students’ perceptions of campus climate, cyberbullying and cultural issues: implications for theory and practice - Souza, S. B.; Veiga Simão, A. M.; Ferreira, A. I.; Costa Ferreira, P. A. N. (Studies in Higher Education, 2018)
This study investigated the influence of campus climate dimensions, namely newcomer adjustment and feelings of well-being on the tendency for victims of cyberbullying to become aggressors, and how cultural issues could influence students’ involvement in situations of cyberbullying. Participants included 979 Portuguese and Brazilian university students who responded to the Cyberbullying Inventory for College Students and the Institutional and Psychosocial Campus Climate Inventory. Moderation analyses revealed that the relationship between being a victim and being an aggressor of cyberbullying was influenced by variables of the psychosocial campus climate and cultural aspects. Student victims from Brazil showed a significant tendency to become aggressors, independently of their level of newcomer adjustment and feelings of well-being, whereas the victims from Portugal tended to break the cycle between being a victim and being an aggressor. Implications for future research, preventive practices and university policies are discussed.